Occurrence and Multi-Locus Genotyping of Giardia duodenalis in Black Goats from Fujian Province, China - Shou-Xiao Huang; Kai Hu; Peng-Fei Fu; Si-Ang Li; Yang Liu; Zhipeng Niu; Dong-Hui Zhou (Animals)
Giardia duodenalis is a zoonotic parasite that causes gastrointestinal diseases in both humans and animals. To evaluate the prevalence and genetic diversity of G. duodenalis in black goats, we collected 539 fecal samples from nine districts in Fujian Province, China. The presence of G. duodenalis was confirmed through nested PCR targeting the SSU rRNA gene, and genotyping was performed at the beta-giardin, glutamate dehydrogenase, and triosephosphate isomerase loci. Among the samples, 115 tested positive, yielding an overall infection rate of 21.34%. Assemblages A and E were identified, with assemblage E being predominant. Statistical analysis revealed significant regional differences in infection rates (p < 0.01), with Zhangzhou exhibiting the highest infection rate (39%) and Fuzhou the lowest (3.13%). No significant differences in infection rates were observed based on age: 24.56% (56/228) for goats <1 year, 14.92% (27/181) for goats 1–2 years, 26.8% (26/97) for goats 2–3 years, and 18.18% (6/33) for goats ≥ 3 years. Similarly, no significant differences were found between sexes: 24.84% (40/161) for males and 19.84% (75/378) for females. Notably, assemblage A, a zoonotic genotype, was detected, indicating a potential risk of cross-species transmission. This study contributes to a deeper understanding of G. duodenalis in black goats and provides critical data for the development of targeted control strategies in Fujian Province.